2022
DOI: 10.1038/s41467-021-27746-y
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state cooling by elastocaloric polymer with uniform chain-lengths

Abstract: Although the elastocaloric effect was found in natural rubber as early as 160 years ago, commercial elastocaloric refrigeration based on polymer elastomers has stagnated owing to their deficient elastocaloric effects and large extension ratios. Herein, we demonstrate that polymer elastomers with uniform molecular chain-lengths exhibit enormous elastocaloric effects through reversible conformational changes. An adiabatic temperature change of −15.3 K and an isothermal entropy change of 145 J kg−1 K−1, obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 29 publications
3
29
0
Order By: Relevance
“…15. If the measurements are performed in an isolated environment, the temperature change will be free from the loading rate dependence which has previously been shown in some research for the elastocaloric polymers [41].…”
Section: Elastocaloric Cooling Performance Of the Printed Elastomersmentioning
confidence: 92%
See 3 more Smart Citations
“…15. If the measurements are performed in an isolated environment, the temperature change will be free from the loading rate dependence which has previously been shown in some research for the elastocaloric polymers [41].…”
Section: Elastocaloric Cooling Performance Of the Printed Elastomersmentioning
confidence: 92%
“…The tests for each sample were conducted in three procedures: one adiabatic stretching-releasing cycle, with a pause to equilibrate with room temperature in between (initial cycle); cyclical stretching and releasing eight times (cyclic process); and one adiabatic stretching-releasing cycle with pauses for temperature equilibration (10th cycle). After the cyclic process, the values of ΔT ad exhibit a significant decrease between the 1st and 10th cycles for the samples due to the irreversible plastic deformation produced during cycling [35,41]. However, the degradation of − ΔT ad is smaller, and for some samples (Ultimaker, KungFu98A, and Z-Flex) the − ΔT ad even increases after the cyclic process.…”
Section: Softening Behavior and Reversible Elastocaloric Effectmentioning
confidence: 96%
See 2 more Smart Citations
“…[22][23][24][25] The eCE has also been characterized in Cu-based 26,27 and Fe-based, 28 magnetic shape memory alloys 29,30 and shape memory polymers. 31,32 Recently, a new elastocaloric alloy (Ni-Mn-Ti-B) with a measured reversible adiabatic temperature change of 31.5 K was discovered, which is one of the largest directly measured caloric effects. 33 Recent reviews of eCMs can be found in the literature.…”
Section: Context and Scalementioning
confidence: 99%